Case Report: Danon Disease: Six Family Members and Literature Review - Wang, Yuanyuan; Jia, Meixue; Guo, Yingjie; Zhang, Ting; Ning, Bin (Frontiers in Cardiovascular Medicine, 2022)
Danon disease is a rare X-linked dominant genetic disorder that manifests with a clinical triad of cardiomyopathy, skeletal myopathy, and intellectual disability. It is caused by mutations in the lysosome-associated membrane 2 (LAMP2) gene. We report one case of Danon disease and his family members, characterized by ventricular pre-excitation, ventricular hypertrophy, abnormal muscle enzymes, and aberrant liver function. All the patients were confirmed to have Danon disease through genetic screening. Relevant literature was reviewed as a reference for the diagnosis and treatment of the disease.